Meningkatkan Keterampilan Motorik Halus melalui Bermain Origami pada Kelompok B di TK DWP DIKPORA Ampenan - Malbitasari Zannatul Abbas; I Made Suwasa Astawa; Muhammad Tahir; Baiq Nada Buahana (Mataram University, 2026)
This study aimed to improve children's fine motor skills through origami play activities in Group B at DWP Dikpora Ampenan Kindergarten. The study was motivated by the insufficient development of children's fine motor skills, as reflected in their difficulties in performing directed movements such as folding paper, pressing fold lines, and coordinating hand and eye movements. To address this issue, origami play activities were implemented as an engaging and educational learning medium. This study employed a Classroom Action Research (CAR) design conducted in two cycles, consisting of the stages of planning, implementation, observation, and reflection. The participants of this study were 17 children in Group B. Data were collected through observation and documentation and analyzed using a quantitative descriptive approach. The findings indicated a gradual improvement in children's fine motor skills across each cycle, increasing from 53.46% in the pre-cycle stage to 65.22% in Cycle I and further to 87.76% in Cycle II, which was categorized as a highly developed level of fine motor skills. Therefore, origami play activities can improve children's fine motor skills and may serve as an alternative learning activity to support fine motor development in early childhood education.